2017
DOI: 10.1262/jrd.2016-129
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of blastocyst development and implantation potential <i>in utero</i> based on the third cleavage and compaction times in mouse pre-implantation embryos

Abstract: Cytokinesis and cell division during pre-implantation embryonic development occur as an orchestrated spatiotemporal program. Cleavage, compaction, and blastulation in pre-implantation embryos are essential for successful implantation and pregnancy. Their alteration is associated with chromosomal imbalance and loss of developmental competence. In this study, we evaluated the time of cleavage and compaction as predictors for in vitro pre- and peri-implantation development and in utero implantation potential by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Time-lapse (TL) imaging of developing embryos offers more accurate quantification of cellular kinetics and cell cycle events than was possible with conventional static morphology assessment. A wide array of kinetic markers have been proposed to be predictive for continued embryonic development and blastocyst formation (8,(10)(11)(12)(13)(14)(15)(16). TL has also revealed the prevalence of specific dysmorphisms such as multinucleation (MU), reverse cleavage (RC), direct uneven cleavage (DUC), and irregular chaotic division (ICD) in human preimplantation embryos (10,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Time-lapse (TL) imaging of developing embryos offers more accurate quantification of cellular kinetics and cell cycle events than was possible with conventional static morphology assessment. A wide array of kinetic markers have been proposed to be predictive for continued embryonic development and blastocyst formation (8,(10)(11)(12)(13)(14)(15)(16). TL has also revealed the prevalence of specific dysmorphisms such as multinucleation (MU), reverse cleavage (RC), direct uneven cleavage (DUC), and irregular chaotic division (ICD) in human preimplantation embryos (10,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In our previous studies, we confirmed a correlation in the developmental competence of preimplantation embryos between blastocyst outgrowth in vitro and implantation in utero [42,43]. We established a novel coculture system with outgrowth and preimplantation embryos, and investigated how this coculture system improved preimplantation and peri-implantation embryonic development both in vitro and in utero.…”
Section: Developmental Competence Of Mouse Blastocysts In Outgrowth Imentioning
confidence: 55%
“…A time-lapse monitoring system has been applied to select transferrable embryos and to predict the developmental competence of preimplantation embryos in human IVF-ET programs. We studied blastocyst development and implantation potential in utero based on the third cleavage and compaction times using a mouse model [43]. Our results provided evidence that analyzing morphokinetics by a time-lapse monitoring system may improve the efficacy of selection of transferrable embryos with high implantation potential in human IVF-ET programs.…”
Section: Developmental Competence Of Mouse Blastocysts In Outgrowth Imentioning
confidence: 95%
See 1 more Smart Citation
“…Aspects of the in vitro trophoblastic outgrowth model, such as activation and spread, are related to proliferation and invasion in in vivo implantation processes [40][41][42][43]. In addition, morphokinetics and metabolism, as evidenced by the trophoblastic outgrowth assay, are correlated with viability and implantation potential [44,45]. In this study, the outgrowth rate after 3 days of culture of blastocysts in the dynamic-O2 (5% to 2%) and low-O2 (5%) groups was superior to that in the high-O2 (20%) group.…”
Section: Discussionmentioning
confidence: 99%